APICAL PERIODONTITIS IN ANTERIOR ROOT-FILLED TEETH: A RETROSPECTIVE STUDY - Mihaela Sălceanu; Agop-Forna Doriana; Cristina Dascălu; Tudor Hamburda; Claudiu Topoliceanu; Georgiana-Andreea Frumuzache; Alice-Teodora; Anca Melian (Romanian Dental Association for Education, 2024)
Aim of study. The aim of the present study was to assess the prevalence of periapical lesions in root-filled lateral teeth as well as the distribution of periapical lesions according to various factors that can influence the therapeutic outcome. Materials and method. The study group included 50 patients (gender: 12 males, 38 females; mean age 51.48 ± 13.218). A total number of 150 anterior root-filled teeth were evaluated at 2-8 yrs. post-treatment. Following the radiographic assessment of the root and its periapical area, the root-canals fillings were classified as adequate and poor. The status of periapical area was assessed on periapical radiographic images. The quality of coronal marginal sealing was assessed as poor or adequate by clinical and radiographic examen. The distribution of apical periodontitis was assessed according to socio-demographical parameters (gender, age groups), location (maxillary, mandibular), follow-up, quality of root canal filling, status of coronal marginal sealing, recurrent caries. Results. The global prevalence of apical periodontitis was 50,7%. The prevalence of apical periodontitis in root-filled anterior teeth was as follows: gender (males- 37,5%; females- 54,2%); age groups (20-39 yrs.- 30%; 40-59 yrs.- 52,9%; ≥60 yrs.- 57,1%); location (maxillary teeth- 42,4%; mandibular teeth- 81,3%). The prevalence of apical periodontitis was 70% in teeth with poor coronal marginal sealing, and 61,4% in teeth with poor root canal fillings. Conclusions. Apical periodontitis was detected in half of the anterior root-filled teeth. The rate of apical periodontitis was significantly increased in maxillary anterior teeth, poor root canals fillings, poor coronal marginal sealing, and root-filled teeth with the presence of recurrent caries.